Mechanistic study of plastic layer permeability during coking of Australian metallurgical coals. (1st January 2023) - Lee, Soonho; Brooks, Brody; Chen, Yixin; Hockings, Kim; Yu, Jianglong; Tahmasebi, Arash
Highlights: Integrated permeability/dilatation and in-situ permeability test facilities were developed. Plastic layer permeability was analyzed under practical coking conditions. Parent coal properties and coking conditions greatly influenced plastic layer permeability. Permeability affected the microstructure transition across the plastic layer. The mass transport between the plastic layer and adjacent layers was a function of permeability. Abstract: The plastic layer permeability of five Australian coals was analyzed using two permeability measurement apparatuses operating under isothermal and thermal gradient induced coking conditions. In addition, the microstructure transitions across the plastic layers of the coals were analyzed using Synchrotron micro-CT. The permeability results and pore structure parameters derived from those analyses were correlated to better understand the mechanisms of plastic layer permeability. The high-rank coking coal with low fluidity showed a low plastic layer permeability over a wide temperature range and the generation of high internal gas pressure (IGP). Among all samples tested, the high-rank coal formed an intermediate plastic layer with the lowest number of isolated pores and the smallest size of open pores. This suggests that the lower deformability of the pore structures brought about by the low fluidity prevented additional pore growth and thus hindered pore interconnectivity. Additionally, it is possible that the low permeability in the resolidfied layer lends to pore expansion due to the difficulty of volatile release, evidenced by the larger volume of open pores within a larger size range of 50–100 µm. It appears that the intermediate plastic layer with less interconnectivity solidified into the expanded open pore structures in the resolidified layer through the driver of high IGP, thus contributing to the low permeability. In addition, the formation of the low permeable barrier seemed to redirect the volatiles evolved from the plastic layer toward the loose coal side, which dramatically reduced the temperature range of the plastic layer during its progression from the wall to the center. These results suggest that the plastic layer permeability is influenced by several factors which affect mass transfer in the plastic layer. As such, various approaches were used in this study to observe phenomena of plastic layer permeability.